Pesantren education system from the perspective of Paulo Freire's thought - Achmad, Syaefudin; Izza, Farah Nuril (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
This article aims to photograph the education system at Pondok Pesantren Edi Mancoro from the perspective of Paulo Freire's thought on education as a liberation practice. This article answers the criticism that pesantren is an educational institution that is rigid, restrictive, static, and exclusive. This research uses a qualitative approach and type of field research. Data collection techniques using observation, interviews, and documentation. Data analysis techniques using data presentation, data reduction, and concluding. The result of the research is a new perspective on education as a liberation practice in Pondok Pesantren Edi Mancoro. The research results show that a small part of the pesantren education system represents Paulo Freire's thought on education as a liberation practice. This research can be a reference for developing a more humanist pesantren education system.